2014
DOI: 10.1021/nn502230m
|View full text |Cite
|
Sign up to set email alerts
|

Bactericidal Activity of Partially Oxidized Nanodiamonds

Abstract: Nanodiamonds are a class of carbon-based nanoparticles that are rapidly gaining attention, particularly for biomedical applications, i.e., as drug carriers, for bioimaging, or as implant coatings. Nanodiamonds have generally been considered biocompatible with a broad variety of eukaryotic cells. We show that, depending on their surface composition, nanodiamonds kill Gram-positive and -negative bacteria rapidly and efficiently. We investigated six different types of nanodiamonds exhibiting diverse oxygen-contai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
166
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 189 publications
(173 citation statements)
references
References 43 publications
6
166
1
Order By: Relevance
“…However, Listeria innocua film contains lysine-derived phospholipids, is amphoteric, and does not have a sufficiently strong net negative charge to attract cationic peptides; therefore, the cell membrane of L. innocua has lower permeability than that of E. coli. In another study, Wehling et al 111 investigated the antibacterial activity of nanodiamonds in various surface structures with different reactive groups and found that these nanomaterials can form covalent bonds with adjacent proteins and molecules on cell walls. Coupling with intracellular components could further restrain key enzymes and proteins, causing a disorder of the bacterial metabolism and, finally, cell death.…”
mentioning
confidence: 99%
“…However, Listeria innocua film contains lysine-derived phospholipids, is amphoteric, and does not have a sufficiently strong net negative charge to attract cationic peptides; therefore, the cell membrane of L. innocua has lower permeability than that of E. coli. In another study, Wehling et al 111 investigated the antibacterial activity of nanodiamonds in various surface structures with different reactive groups and found that these nanomaterials can form covalent bonds with adjacent proteins and molecules on cell walls. Coupling with intracellular components could further restrain key enzymes and proteins, causing a disorder of the bacterial metabolism and, finally, cell death.…”
mentioning
confidence: 99%
“…Such biofilm disrupting activity had not been observed previously for other glyco-nanoparticles (glyco-NPs) such as glycofullerenes, goldbased glyco-NPs or for other multivalent mannose-derived molecules [2] and [40]. Wehling et al have concluded that the bactericidal activity of diamond particles is directly linked to their surface chemistry, being thus the driving force of antibacterial effects [37].…”
Section: Introductionmentioning
confidence: 94%
“…ND-menthol as well as ND-OH particles used as control have both positive zeta-potential (Table 1). More recently, Wehling et al [37] studied the bactericidal activity of partially oxidized NDs. Their experiments suggested that the antibacterial activity of NDs is linked to the presence of partially oxidized and negatively charged surfaces, specifically those containing acid anhydride groups.…”
Section: Fig 2 (A) Ftir Spectra Of Nd-oh (Black) and Nd-menthol (Rementioning
confidence: 99%
See 1 more Smart Citation
“…[5][6][7] Over the course of the past few years, major strides have been made in TiO 2 -nanosystem surface modification, due to a lot of significant progress in electrochemistry, catalysis, energetics, and corrosion. [8][9][10] Many researchers have applied electrochemical anodization technique to create TiO 2 nanotubes or nanopores on the surface of biomaterials to stimulate cell proliferation, cell adhesion, or mineralization of osteoblasts in vitro, and have achieved some good results. [11][12][13] In addition, it has been proved that TiO 2 nanotubes can generate better OI in vivo, due to their biomimetic scale and bone-resembling elasticity.…”
mentioning
confidence: 99%